Salted-Fish industry in Roman Lusitania: Trade Memories between Oceanus and Mare Nostrum - Bombico, Sónia (2016)
Initiated by Augustus, Rome’s Atlantic policy seems to have been consolidated in the age of Claudius, with the acknowledgement of the economic potential offered by the Atlantic region. It is in this context that we must understand the development of the salted-fish industry in Lusitania. In the same geographical contexts, and in close relationship with fish-processing factories, are known about 20 pottery centres producing amphorae, located in the regions of Peniche, Sado and Tejo valleys, and the coasts of Alentejo and Algarve. This production extended in time beyond the end of the Western Roman Empire and up to the end of the 5th and 6th centuries, according to the archaeological data of some amphora kilns and fish-processing sites. The identification of Lusitanian amphorae in distant consuming centres and several shipwrecks in the Mediterranean basin confirm the long-distance commerce and the total integration of this “peripheral” region into the trade routes of the Roman Empire.